STUDY ON EFFECT OF STRECHING EXERCISES AND PRANAYAMA ON HEART RATE VARIABILITY (HRV) IN HEALTHY VOLUNTEERS - SHANKARAPPA.V; PRABHA. V (International Journal of Pharma and Bio Sciences, 2013)
Yoga is a science practiced in India over thousands of years. Besides spiritual achievements, the practice of yoga is accompanied by a number of psycho-physiological beneficial effects in the body. Heart rate variability (HRV) has been established as a non-invasive tool to measure continuous interplay between sympathetic and parasympathetic influences on heart rate and yields information about autonomic flexibility.HRV is commonly described by standard deviation of intervals between successive R waves (SDNN) of cardiac cycle. This study was designed to study the effects of pranayama and stretching exercises on HRV in yoga practitioners. Study group comprises of 50 yoga practitioners of same socio –economical background and age matched (between 25 –50yrs) in yoga center. HRV was recorded for 5 min in supine position in a quiet room by using (CARDIART 8408 VIEW) HRV machine. These data obtained were tabulated and statistically analyzed using paired t-test and Pearson’s correlation test. HRV after yoga: mean SDNN 0.089±0.039 in yoga practitioners, before yoga SDNN mean 0.0326±0.0071of mean age 45.1±13.13 years. HRV was significantly higher in regular pranayama and stretching exercise practitioners (p< 0.001). There was a statistically significant increase in HRV in regular yoga practitioners indicating parasympathetic dominance. Asanas and pranayama causes cue controlled relaxation and biofeedback shift of autonomic balance towards an increase of vagal activity..